Effectiveness of enrichment activities through using software program for second graders in Conversation article (Journal Of Educational and Psychological Researches, 2013)
Today we are witnessing huge scientific and technical progress so we need more skills and methods of thinking that needs to be acquired by the teacher, as the importance of computers in education  there are  many teachers  suffering  of the difficulty in teaching for pupils . researchers tried to  find a good suitable way with the technological  interests for now which represent by  computer design software and the introduction of enrichment activities in the curriculum because it is one of a contemporary trends for the development of the Arabic language with various levels of education and knowing if this program has negative or positive impact.So  researchers presented  the research  Effectiveness of enrichment activities  through using software program for second graders in Conversation article with null hypothesis  which research sample reached to (60) students in a intentional way distributed  into two groups    ( experimental group and the control group ) and the researchers used  anterior and posterior test , who prepared  the appropriate statistical means for research, results showed that there are presence of statistically significant differences between anterior and posterior test  in performance and achievement between the experimental group and the control group  that went to experimental group which has studied the use of a software program.